2021
DOI: 10.1186/s43045-021-00151-3
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and clinical correlates of parenting style among parents having ADHD children: a cross-section study

Abstract: Background ADHD affects 7.8% of the school-aged population, making it one of the most common childhood brain illnesses. It is characterized by abnormally high levels of inattention, activity, and impulsivity at a young age. Being a parent of a child with ADHD is a real challenge, as the parents tend to be more disapproving, critical, and provide more impulse control directions; such parenting style can have an impact on the illnesses course, accentuate its signs and symptoms, and lead to second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
2
2
Order By: Relevance
“…According to the study conducted by El-Deen et al ( 2021), a minority of dads (27.1%) held professional occupations, while a majority of mothers (64.6%) were engaged in domestic duties as housewives. Additionally, a significant proportion of the families (45.8%) belonged to the middle social class [22]. The results of this study contradicted the findings of Malek and Amiri (2012), who regarded maternal employment as a predictor variable for ADHD [23].…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…According to the study conducted by El-Deen et al ( 2021), a minority of dads (27.1%) held professional occupations, while a majority of mothers (64.6%) were engaged in domestic duties as housewives. Additionally, a significant proportion of the families (45.8%) belonged to the middle social class [22]. The results of this study contradicted the findings of Malek and Amiri (2012), who regarded maternal employment as a predictor variable for ADHD [23].…”
Section: Discussioncontrasting
confidence: 97%
“…Furthermore, the present study's results do not yield statistically significant evidence concerning the association income status with parenting style. This finding contradicts the findings of El-Deen et al's (2021) study, which demonstrated a positive relationship between ADHD children with fathers and mothers engaged in professional employment and positive parenting practices [22].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Communities must dedicate resources to psychosocial treatment for it to show a significant improvement in children's functioning and health. 5 BPT is an evidencebased psychosocial treatment that focuses on increasing positive and decreasing negative parenting through instruction and practice in effective caregiving strategies. It has been developed for parents of children with ADHD and associated behaviour problems.…”
mentioning
confidence: 99%